The Karate princess - Strong, Jeremy; Abel, Simone, illus (London : Puffin, 2002)
Belinda, the youngest of sixteen, buy by no means the prettiest, is not an ordinary princess. can she win handsome prince or will she even want to?
Keywords: Karate; Princesses